2015
DOI: 10.1093/nar/gkv146
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Escherichia coli SeqA complexes organize the newly replicated DNA at a considerable distance from the replisome

Abstract: The Escherichia coli SeqA protein binds to newly replicated, hemimethylated DNA behind replication forks and forms structures consisting of several hundred SeqA molecules bound to about 100 kb of DNA. It has been suggested that SeqA structures either direct the new sister DNA molecules away from each other or constitute a spacer that keeps the sisters together. We have developed an image analysis script that automatically measures the distance between neighboring foci in cells. Using this tool as well as direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
39
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 70 publications
5
39
2
Order By: Relevance
“…The script is run under Fiji and uses Find Maxima as a tool for detecting the center of mass of foci within regions of interest, i.e., within cells. It is possible to distinguish foci that are closer than the resolution limit of fluorescence microscopes when measuring the distance between spots in two different channels (53,77,78). Thus, in this study, we were able to present measurements of focus distances below the resolution limit of our microscopy system.…”
Section: Methodsmentioning
confidence: 87%
See 4 more Smart Citations
“…The script is run under Fiji and uses Find Maxima as a tool for detecting the center of mass of foci within regions of interest, i.e., within cells. It is possible to distinguish foci that are closer than the resolution limit of fluorescence microscopes when measuring the distance between spots in two different channels (53,77,78). Thus, in this study, we were able to present measurements of focus distances below the resolution limit of our microscopy system.…”
Section: Methodsmentioning
confidence: 87%
“…We have previously shown that there is an average distance of 200 to 300 nm between the replisome and the large SeqA structure trailing it, which may correspond to several thousands of base pairs of DNA (53). Since H-NS is able to form hairpin loops on DNA in vitro, we wondered whether an increased distance between SeqA and the replisome could be observed in H-NS mutant cells in vivo as a result of decondensed DNA between the two structures.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations